An assessment of Individual, community and state-level factors associated with inadequate iodised salt consumption among pregnant and lactating women in Nigeria - Yusuf Olushola Kareem; Edward Kwabena Ameyaw; Roberta Mensima Amoah; Oyelola A Adegboye; Sanni Yaya (BMC, 2023)
Abstract Background Iodine deficiency is the most common cause of thyroid disease, and in its severe form can result in cretinism; the impairment of the brain development of a child. Pregnant and breastfeeding women's daily iodine requirement is elevated due to physiological changes in iodine metabolism, requiring up to double the iodine intake of other women. Although Nigeria was the first African country to be declared iodine sufficient in 2007, recent evidence has shown that only about seven in ten households consume salt with adequate iodine content (≥ 15 ppm), with variation across states. The study aimed to assess the Individual- and household-, community- and state-level factors associated with inadequate iodised salt consumption among pregnant women and breastfeeding mothers in Nigeria. Methods This study utilised the Multiple Indicator Cluster Survey to assess factors associated with inadequate iodised salt consumption among 4911 pregnant women and breastfeeding mothers in Nigeria. The descriptive analysis was presented using frequencies and percentages. The prevalence of adequate and inadequate iodised salt consumption with their 95% confidence interval were computed. Several multi-level mixed effect log-binomial logistic regressions were used to explore the factors associated with inadequate iodised salt consumption. The Loglikelihood, Akaike Information Criterion and Bayesian Information Criterion were used to assess the goodness of fit of the models. All analyses were adjusted for the complex survey design and analysed using Stata 15.0 at p < 0.05. Results The prevalence of inadequate iodised salt consumption among pregnant and breastfeeding mothers was 35.2% (95% CI: 33.1-37.5). Inadequate consumption of iodised salt was highest among pregnant and breastfeeding women aged 45-49 years (48.2%; 95%CI: 37.8-58.8), as well as those with non-formal education (52.7%; 95%CI: 47.7-57.6) and no education (34.6%; 95%CI: 31.3-38.1). Our findings revealed that pregnant and breastfeeding women living in the poorer, middle, richer and richest quintiles were 32%, 47%, 35% and 62% less likely to consume salt with inadequate iodine compared to those in the poorest households. Those with non-formal education were 1.8 times (95%CI: 1.36-2.42) more likely to consume salt with deficient iodine than those without education. Pregnant and breastfeeding mothers residing in moderately and most deprived communities were 3.5 (95%CI: 2.57-4.73) and 4.7 times (95%CI: 3.38-6.55) more likely to consume salt with inadequate iodine than those from least deprived communities. Women in the Northwestern region and those from the Southwestern region were 4.0 and 3.5 times, respectively, more likely to consume salt with inadequate iodine compared to pregnant and breastfeeding women residing in the North-Central region. Conclusions The study has shown that inadequate consumption of iodised salt dominates among older pregnant and breastfeeding women. Also, women with non-formal education have higher prospects of consuming salt with lesser iodine. There is a need to enhance women's economic opportunities and empowerment as well as sensitisation on their nutritional requirements during pregnancy and breastfeeding. Both formal and non-formal educational initiatives on nutrition are extremely important and should be prioritised by the Nigerian government in its efforts to encourage the consumption of iodised salt among pregnant and lactating mothers. Additionally, health promotion interventions that seek to advocate iodised salt intake must be prioritised by the actors in the health sector.